2012
DOI: 10.1007/s10072-012-1045-6
|View full text |Cite
|
Sign up to set email alerts
|

Is migraine a risk factor for the occurrence of eating disorders? Prevalence and biochemical evidences

Abstract: The eating disorders (ED), anorexia nervosa (AN) and bulimia nervosa (BN), are severe psychiatric and somatic conditions occurring mainly in young woman. Although the aetiology is largely unknown, same evidences suggest that biological and psychological factors play a relevant role in the pathogenesis, along with monoamine, indole and same hypothalamic hormonal dysfunctions. Migraine is characterized by similar metabolic and psychological anomalies suggesting that a possible relationship exists between the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
(20 reference statements)
0
14
0
Order By: Relevance
“…Women with a lifetime diagnosis of an eating disorder were twice as likely to report a history of migraine as were women from the general population: thus the association between migraine and eating disorders suggested by previous studies was confirmed. 14,15 However, this relationship appeared to be mediated by MDD. We observed that women with both an eating disorder and MDD, had a very high prevalence of migraine (36%).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Women with a lifetime diagnosis of an eating disorder were twice as likely to report a history of migraine as were women from the general population: thus the association between migraine and eating disorders suggested by previous studies was confirmed. 14,15 However, this relationship appeared to be mediated by MDD. We observed that women with both an eating disorder and MDD, had a very high prevalence of migraine (36%).…”
Section: Discussionmentioning
confidence: 87%
“…14 In another study, 74% of eating disorder inpatients reported migraine. 15 Although both studies lacked a well-defined control population, the reported prevalences clearly exceed those in the general population. A third study did not find an increased prevalence of migraine among eating disorder patients, 16 but the control group was genetically related to the probands (sisters) and thus not suitable for assessing true populationlevel risk.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…One of the most severe disorders reminiscent of CR is anorexia nervosa (AN), which has the highest rate of mortality among all mental disorders (97) and is the most prevalent in young women (98). From the physiological and psychological points of view, there are common features between people suffering from AN and those practicing CR (28, 99).…”
Section: Sirt1 Influences Neurological Processes: Memory Mood and Bmentioning
confidence: 99%
“…Moreover, a higher migraine prevalence in metabolic syndrome patients was demonstrated comparing to the general population (Guldiken et al, 2009). On the other hand, there is also a potential association with eating disorders, with a high prevalence of migraine in woman affected by anorexia or bulimia nervosa (D'Andrea et al, 2012). In rodents, neuropeptides like orexin and neuropeptide Y involved in the regulation of feeding have been proposed to regulate the trigeminovascular system (Hoffmann et al, 2015, Holland et al, 2006, Martins-Oliveira et al, 2016).…”
Section: Introductionmentioning
confidence: 99%